2015
DOI: 10.1152/ajplung.00331.2014
|View full text |Cite
|
Sign up to set email alerts
|

The cardiac protein αT-catenin contributes to chemical-induced asthma

Abstract: Ten to 25% of adult asthma is occupational induced, a subtype caused by exposure to workplace chemicals. A recent genomewide association study identified single-nucleotide polymorphisms in the cardiac protein αT-catenin (αT-cat) that correlated with the incidence and severity of toluene diisocyanate (TDI) occupational asthma. αT-cat is a critical mediator of cell-cell adhesion and is predominantly expressed in cardiomyocytes, but its connection to asthma remains unknown. Therefore, we sought to determine the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 21 publications
1
28
1
Order By: Relevance
“…There are three forms of α-catenin: neural (N), epithelial (E) and testis/heart (T) [8]. There is an increasing recognition that in addition to the well-established role in cell adhesion, α-catenin regulates multiple pathways controlling cell density, polarity, proliferation and apoptosis [911].…”
Section: Introductionmentioning
confidence: 99%
“…There are three forms of α-catenin: neural (N), epithelial (E) and testis/heart (T) [8]. There is an increasing recognition that in addition to the well-established role in cell adhesion, α-catenin regulates multiple pathways controlling cell density, polarity, proliferation and apoptosis [911].…”
Section: Introductionmentioning
confidence: 99%
“…Based on αT-catenin expression pattern, it is unclear how this largely cardiac-restricted α-catenin isoform might affect lung physiology. Interestingly, it was recently discovered that αT-catenin is expressed in lung within the cardiac sheath of pulmonary veins (Folmsbee et al, 2014). The same group found that αT-cat-null mice have altered lung mechanics demonstrated by increased pressure-volume curve area suggesting loss of αT-catenin affects lung hysteresis.…”
Section: αT-catenin Function Outside the Heartmentioning
confidence: 99%
“…However, with age, these mice develop cardiomyopathy with decreased ejection fraction(7), consistent with the abundant expression of αT-cat in heart, and its recent link to familial arrythmogenic right ventricular cardiomyopathy(8). Our group has previously shown that αT-cat is present in the lungs, but in contrast to the more ubiquitously expressed αE-cat (found in lung epithelial, smooth muscle and endothelial cell types), αT-cat is restricted to the cardiomyocyte cell layer that surrounds pulmonary veins(9). Pulmonary veins have long been observed to become inflamed in murine models of asthma(10), but their role in regulating airway inflammation is largely not known, perhaps because the pulmonary veins develop separately from the sheath containing the arteries and airways of the lung(11).…”
Section: Introductionmentioning
confidence: 99%
“…Pulmonary veins have long been observed to become inflamed in murine models of asthma(10), but their role in regulating airway inflammation is largely not known, perhaps because the pulmonary veins develop separately from the sheath containing the arteries and airways of the lung(11). Despite their developmental independence, we have shown that subsets of airways can be found adjacent to the pulmonary veins in the mouse lung(9). …”
Section: Introductionmentioning
confidence: 99%